Low-temperature magnetism in the honeycomb systems SrLn2O4(Review Article) - Petrenko, O.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
Recent progress in the understanding of the complex magnetic properties of the family of rare-earth strontium oxides, SrLn2O4, is reviewed. These compounds consisting of hexagons and triangles are affected by geometrical frustration and therefore exhibit its characteristic features, such as a significant reduction of magnetic ordering temperatures and complex phase diagrams in an applied field. Some of the observed features appear to be rather remarkable even in the context of the unusual behavior associated with geometrically frustrated magnetic systems. Of particular interest is the coexistence at the lowest temperature of different magnetic structures (exhibiting either long or short-range order) characterized by different propagation vectors in materials without significant chemical or structural disorder.